Soluble phosphorus rich compost by aerobic solid-state fermentation of chicken bone-containing food waste with Aspergillus niger - Ong, Lu Ki; Angelio, Ricardo; Indrayani, Clarissa; Riadi, Lieke (Jurnal Rekayasa Proses, 2025)
Food waste has become a concern in solid waste management due to its high bulk volume and production rate. Without good management, food waste piling may result in foul odor, global warming by methane emission and even an epidemic. Composting is a method usually employed to process food waste. However, this method often took a long period and selective to organic waste such as leafy materials or fruit waste. Bone is a food waste that is rich in phosphorus, a chemical substance that is required to make various useful products such as fertilizer, battery, detergent, etc. This study investigates the characteristics of food waste compost containing chicken bone and various domestic organic food waste that was processed through aerobic solid-state fermentation using Aspergillus niger. The composting process was monitored over a 28-day period at 28°C. The resulting compost was characterized under various physicochemical parameters, including pH and nutrient composition. The findings demonstrated that Aspergillus niger effectively released phosphorus from bone while degraded organic matter in just a week, resulting in significant reductions in unprocessed waste volume and the production of a stable, nutrient-rich compost in a short time. Additionally, the compost was successfully induced better growth on corn seed compared to the food waste pile and naturally composted food waste. These results suggest that Aspergillus niger-mediated aerobic solid-state fermentation is a viable and efficient method for converting food waste into high-quality compost, promoting sustainable waste management and agricultural practices.